Modern theoretical and legal amendments to the constitution of the Russian Federation - Melnikov, Victor Yu.; Seregin, Andrei V.; Hmelchenko, Elena G.; Tsechoyev, Valery K.; Selivanova, Evgeniya S. (Opción, 2020)
The study aims to investigate modern theoretical and legal amendments to the constitution of the Russian Federation via the dialectical method of cognition of social and legal phenomena and concepts in their development and interdependence. As a result, the competence of the State Council, in particular the right to determine the main directions of domestic and foreign policy, comes into direct conflict with the prerogatives of the President. In conclusion, Formal and theoretical contradictions of the Constitution of the Russian Federation pose a threat to the territorial unity, independence, social, political and legal stability of the state